THE UTILIZATION OF EXPRESSIVE WRITING IN COUNSELING IN INDONESIA - Nur'aini Safitri; Nurhafiza (CV. TOTUS TUUS, 2026)
Expressive Writing is a therapeutic technique that encourages individuals to explore their thoughts, emotions, and experiences through writing. This technique is especially beneficial for individuals who have difficulty expressing themselves or expressing their problems verbally in the counseling process. This study uses the literature review method with the aim of finding out the use of expressive writing in counseling in Indonesia. Data collection was carried out by conducting a review of various literature relevant to the research study using the keywords